Emotional arousal when watching drama increases pain threshold and social bonding - Dunbar, R; Teasdale, B; Thompson, J; Budelmann, F; Duncan, S; van Emde Boas, E; Maguire, L (Royal Society, 2016)
Fiction, whether in the form of storytelling or plays, has a particular attraction for us: we repeatedly return to it and are willing to invest money and time in doing so. Why this is so is an evolutionary enigma that has been surprisingly underexplored. We hypothesize that emotionally arousing drama, in particular, triggers the same neurobiological mechanism (the endorphin system, reflected in increased pain thresholds) that underpins anthropoid primate and human social bonding. We show that, compared to subjects who watch an emotionally neutral film, subjects who watch an emotionally arousing film have increased pain thresholds and an increased sense of group bonding.